Setting the surgical wound care agenda across two healthcare districts: A priority setting approach. Issue 5 (October 2020) - Gillespie, Brigid M.; Walker, Rachel; Lin, Frances; Roberts, Shelley; Nieuwenhoven, Paul; Perry, Jodie; Birgan, Sean; Gerraghy, Elizabeth; Probert, Rosalind; Chaboyer, Wendy
ABSTRACT: Introduction: Surgical wound care requires an interprofessional approach; however, there is considerable variation in practice and a lack of robust evidence to guide clinicians. Thus, it is important to identify priority areas from the perspectives of end-users to target efforts to both generate and implement high quality evidence. Objective: To rank the top four priority questions in wound management across two health districts to inform future research and implementation efforts in wound care. Methods: A multisite modified nominal group technique was used to build consensus. Two interactive two-hour workshops were held across two health services districts. Participants were recruited from nursing, allied health and medicine. In preparation for the workshops, a standard operating procedure was developed, and 25 wound care priority questions identified, a priori. Descriptive statistics were used to analyse workshop data. Results: Across districts, 38 health professionals participated in the workshops. From a list of 25 clinical questions, the top 10 were determined, and from these, the top four. The number one priority question identified by 23/38 (60.5%) participants across districts related to patients' understanding/knowledge of their wound treatment. The number two priority question 15/38 (39.5%) participants voted on focussed on patient involvement in wound care. Conclusions: Overall, the priority questions reflect the need to encourage patient participation in wound care. These wound care priorities can be used to inform future research and improvement efforts in wound care.